Mechanical properties of APbX3 (A = Cs or CH3NH3; X = I or Br) perovskite single crystals. (6th October 2015) - Rakita, Yevgeny; Cohen, Sidney R.; Kedem, Nir Klein; Hodes, Gary; Cahen, David
Abstract: Abstract : The remarkable optoelectronic and especially photovoltaic performance of hybrid organic–inorganic perovskite (HOIP) materials drives efforts to connect materials properties to this performance. From nano-indentation experiments on solution-grown single crystals we obtain elastic modulus and nano-hardness values of A Pb X 3 ( A = Cs, CH3 NH3 ; X = I, Br). The Young's moduli are ~14, 19.5, and 16 GPa, for CH3 NH3 PbI3, CH3 NH3 PbBr3, and CsPbBr3, respectively, lending credence to theoretically calculated values. We discuss the possible relevance of our results to suggested "self-healing", ion diffusion, and ease of manufacturing. Using our results, together with literature data on elastic moduli, we classified HOIPs amongst the relevant material groups, based on their elastomechanical properties.